Perubahan Geopolitik dan Ketahanan Nasional: Sebuah Penjelajahan Teoretikal - Kusnanto Anggoro (Jurnal Lemhannas RI, 2017)
Technology has played an important role, even a driving force, in geopolitical changes throughout history. Transportation, communication, information are always at the core of inter-state exchanges such as trade and wars, as well as that of inter-cultural relations amongst societal groups. Technology imposed geographic contraction, shortened distance, and as such at the driving force for social harmony, political order, and national security. In some cases, however, this technological nevessities whack the wall of conservative strategic culture. Indonesia’s strategic culture seems to remain in the shadow of colonial past and/or turbulence domestic during formatting years of the unitary state; and as such strengthen geographic boundary as border rather than bridge to the outside world. Geostrategic conception is therefore inward looking. Challenges abound. While nation building is in essence a long term promotional approach, the challenges of state building in the immediate future of Indonesia is to be a democratic yet responsive, anticipatory state. Form strategic point of view, this requires efficient use national resources and effective exercise of national instruments. Geopolitical changes pose serious challenges to national resilience. A more creative and imaginative reconstitution of national resilience policy, including its integration into national security policy, should enhance the likely for Indonesia to survive, progress, and develop into a modern nation-state.